2018
DOI: 10.1158/1538-7445.sabcs17-gs6-07
|View full text |Cite
|
Sign up to set email alerts
|

Abstract GS6-07: EMBRACA: A phase 3 trial comparing talazoparib, an oral PARP inhibitor, to physician's choice of therapy in patients with advanced breast cancer and a germline BRCA mutation

Abstract: Background: Talazoparib (TALA) is a highly potent, dual-mechanism PARP inhibitor that inhibits the PARP enzyme and effectively traps PARP on single-stranded DNA breaks, preventing DNA damage repair and causing cell death in BRCA1/2-mutated cells. Methods: EMBRACA is an open-label, randomized, 2-arm, phase 3 trial comparing the efficacy and safety of TALA (1 mg/day) with standard single-agent physician's choice of therapy (PCT) (capecitabine, eribulin, gemcitabine, or vinorelbine) in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 0 publications
0
42
0
4
Order By: Relevance
“…Both studies showed improvement of median PFS with the PARP inhibitor of ~ 3 months and greater tolerability, with no overall survival benefit evident as yet. Among patients with measurable disease, the objective response rates were approximately 60% with the PARP inhibitor compared to approximately 30% in physician choice (need to check talazaparib) [18,19]. The FDA approved olaparib for the treatment of germline BRCA1/2 metastatic breast cancer in January 2018.…”
Section: Germline Brca1 and Brca2 Mutation Status As A Hr Deficiency mentioning
confidence: 99%
“…Both studies showed improvement of median PFS with the PARP inhibitor of ~ 3 months and greater tolerability, with no overall survival benefit evident as yet. Among patients with measurable disease, the objective response rates were approximately 60% with the PARP inhibitor compared to approximately 30% in physician choice (need to check talazaparib) [18,19]. The FDA approved olaparib for the treatment of germline BRCA1/2 metastatic breast cancer in January 2018.…”
Section: Germline Brca1 and Brca2 Mutation Status As A Hr Deficiency mentioning
confidence: 99%
“…Several early phase studies with the other PARPis demonstrated similar signals of efficacy in BRCAmutant breast cancer ( Table 2). [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] Multiple phase 2 studies further demonstrated activity of olaparib in patients who had metastatic breast cancer with germline BRCA mutations. [30][31][32] In a phase 2 study, Tutt et al investigated the effects of olaparib monotherapy in 54 patients who had centrally confirmed, germline BRCA-mutant breast cancer.…”
Section: Single-agent Parpis In Metastatic Breast Cancermentioning
confidence: 99%
“…Recently, the activity of talazoparib in BRCA ‐mutant breast cancer was demonstrated in the phase 3 EMBRACA trial . Initial results from that trial demonstrated a median PFS of 8.6 months in patients who received talazoparib compared with 5.6 months in those who received chemotherapy ( P < .0001).…”
Section: Clinical Development In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Despite longer PFS and higher response rates, the median duration of response was only 5.4 months and OS, at an interim analysis after 51% of the projected events, was not significantly different between groups (hazard ratio, 0.76; P = .10). 13 Despite impressive responses and PFS benefit, development of resistance to PARPi was almost ubiquitous, hampering the duration of response and perhaps even OS. Furthermore, PFS benefit was in the range of 2-4 months with PARPi, even in germline BRCA-mutant patients.…”
Section: P Oly ( Adp -Ribos E) P Olymer a S E Inhib Itor S In B Re mentioning
confidence: 99%